Strength characteristics of mortar incorporating chemical additives and brown glass waste as a partial substitute for sand - Aravinda Reddy, Thiakarajan (2024)
This research focuses on addressing the impact of using brown glass powder as a partial sand replacement in cement mortar, in response to environmental concerns and resource depletion. The study investigates how varying concentrations of chemical additives affect the compressive strength, microstructure, and water absorption of the mortar with brown glass powder to optimize its performance. By exploring the effects of different chemicals and concentrations, it aims to understand how these factors influence both the fresh and hardened properties of mortar treated with brown glass waste. Brown glass waste was substituted for sand at 0%, 25%, 50%, 75%, and 100% and treated with Hydrochloric Acid (HCl), Calcium Hydroxide (Ca(OH)₂), and Calcium Nitrate (Ca(NO₃)₂) in concentrations of 0.05 M and 0.1 M. The mortar samples were subjected to flow table test, compression test, water absorption test, Scanning Electron Microscopy (SEM) analysis and Energy Dispersive X-ray (EDX) analysis. Results demonstrated that replacing sand with up to 25% glass powder, combined with 0.05 M Calcium Nitrate, yielded the highest compressive strength. The SEM analysis revealed that higher glass powder content reduced microstructural cracks and pores when incorporating Calcium Hydroxide and Calcium Nitrate. However, when incorporating Hydrochloric Acid, it negatively affects the microstructure of the mortar. The findings of this study suggest that the mortar incorporating 0.05 M Calcium Nitrate with 25% brown glass waste is the most optimal combination with the highest compressive strength, optimal workability, and lower water absorption.